2021
DOI: 10.1152/jn.00034.2021
|View full text |Cite
|
Sign up to set email alerts
|

An examination of a potential organized motor unit firing rate and recruitment scheme of an antagonist muscle during isometric contractions

Abstract: The primary purpose of the present study is to determine if an organized control scheme exists for the antagonist muscle during steady isometric torque. A secondary focus is to better understand how firing rates of the antagonist muscle changes from a moderate- to higher-contraction intensity. Fourteen subjects performed two submaximal isometric trapezoid muscle actions of the forearm flexors that included a linearly increasing, steady force at both 40% and 70% maximum voluntary contraction, and linearly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 71 publications
6
11
0
Order By: Relevance
“…In addition, using MMG MPF (12), and MMG AMP and MPF (19) to quantify coactivation, it has been shown that there were similar responses between agonist and antagonist muscles during fatiguing isometric contractions of the flexors/extensors of thumb and forearm, respectively. The results of this study extended the findings of Lévénez et al (25), De Luca and Mambrito (12), and Reece and Herda (30) to maximal, reciprocal, fatiguing, isokinetic forearm flexion, and extension muscle actions. The parallel fatigue-induced responses observed within each muscle during both movements may be attributable to a descending "common drive" to the agonist and antagonist muscles (12,28,30) by the musculocutaneous and radial nerves, which both stem from the C6 spinal nerve (6).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, using MMG MPF (12), and MMG AMP and MPF (19) to quantify coactivation, it has been shown that there were similar responses between agonist and antagonist muscles during fatiguing isometric contractions of the flexors/extensors of thumb and forearm, respectively. The results of this study extended the findings of Lévénez et al (25), De Luca and Mambrito (12), and Reece and Herda (30) to maximal, reciprocal, fatiguing, isokinetic forearm flexion, and extension muscle actions. The parallel fatigue-induced responses observed within each muscle during both movements may be attributable to a descending "common drive" to the agonist and antagonist muscles (12,28,30) by the musculocutaneous and radial nerves, which both stem from the C6 spinal nerve (6).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in this study, it is possible that the parallel fatigue-induced responses in activation between the agonist and antagonist muscles were the result of a “common drive” to provide elbow joint stability (12,13,28). Furthermore, the current findings, in conjunction with those of previous studies (12,19,25,30), suggested that although coactivation can be examined using EMG, the simultaneous examination of MMG responses may be helpful in assessing coactivation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The analysis of MU firing rates in earlier phases (0-200 ms) of torque development would add considerably to our understanding of differences in MU control schemes between the contractions performed in the present study (Maffiuletti et al, 2016) MUs within the observed action potential ranges (Contessa et al, 2018;Hu et al, 2013;Miller et al, 2018Miller et al, , 2019Miller et al, , 2020Reece & Herda, 2021;Sterczala et al, 2018b). Figures 9 and 10 illustrate the MFR versus MUAP AMP relationships along with 95% confidence intervals for each subject and muscle included in the firing rate ANOVA models.…”
Section: Discussionmentioning
confidence: 91%
“…This MU firing rate versus action potential amplitude relationship has been demonstrated in submaximal contractions in both agonist (Hu et al, 2013;Miller et al, 2019;Trevino et al, 2019) and antagonist muscles (Reece & Herda, 2021). In order to gain a better understanding of activation of the agonist (Miller et al, 2018(Miller et al, , 2019(Miller et al, , 2020Parra et al, 2020;Sterczala et al, 2020;Trevino et al, 2019) and antagonist muscles (Reece & Herda, 2021), previous studies have quantified MU firing rates as a function of action potential amplitude on a subject-by-subject and contraction-by-contraction basis. Therefore, we examined firing rates and action potential amplitudes of MUs recorded from the biceps brachii (BB) and triceps brachii (TB) during isometric explosive and ramp MVCs of the elbow flexors.…”
Section: New Findingsmentioning
confidence: 91%